Who has given up on mathematics? A data analysis - Ko, Ho Kyoung; Choi, Suyoung; Kaji, Shizuo (Asia Pacific Education Review, 2021)
The newly coined term supoza (giving up mathematics, 수포자, 數抛者) describes a critical social issue that needs to be addressed in South Korea’s educational policy. Although the term has not received precise definition, it refers to students who have given up on learning mathematics. A precise definition would require detailing the current supoza situation and identifying its characteristics. This study therefore conducted a statistical investigation of commonalities among students who have given up on learning mathematics; the study results revealed that these students can be characterized by their affective domain for mathematics learning. We found that a statistical model could determine the likelihood that a particular student would report having given up mathematics based on responses to questions related to the affective domain of mathematics learning. This aspect suggests the possibility of understanding supoza with the exclusive use of affective factors and emphasizes the significance of the affective domain of mathematics learning. Additionally, this study provides a working example to show how exploratory analysis using big data can be used in relation to mathematical education.
Keywords: Affective domain; Machine learning; Mathematics; Supoza